VIRTUES AND CHARACTER STRENGTHS OF KAZ AND NINA'S CHARACTERS IN THE NOVEL SIX OF CROWS - Muhamad Bahtiar Reza; Dwi Nitisari (Universitas Gunadarma, 2022)
This research was aimed to find out and compare the virtues and character strengths of Kaz and Nina's characters in the novel Six of Crows. The researchers used Peterson and Seligman's theory of virtue and character strengths. This research used the qualitative method. In the analysis of the 285 data found in this research, the researchers found 161 data indicating Kaz's virtues and character strengths and 124 data indicating Nina's virtue and character strengths. Both characters possess all six virtues: wisdom and knowledge, courage, humanity, justice, temperance, and transcendence. The researchers found that Kaz and Nina possess twenty-one-character strengths. Kaz possesses all of the character strengths but love, citizenship, and gratitude, while Nina possesses all but fairness, leadership, and forgiveness and mercy. Based on the research findings, the researchers concluded that both Kaz and Nina possess all the virtues mentioned by Peterson and Seligman. Additionally, both characters possess the same number of character strengths which is twenty-one-character strengths, even though their character strengths are relatively different.